Cathode structure with high porosity and high electro-catalytic performance and preparation method thereof
Porous nickel structures were prepared by plasma spraying and chemical activation, and Mn-doped ZnCoP coating was deposited on its surface, which solved the problem of insufficient porosity and catalytic activity of traditional cathode structures, and achieved efficient and stable electrocatalytic performance, reducing the It is suitable for electrolyzing seawater hydrogen production technology.
Patent Information
- Application Number
- CN202411295120.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-15
- Publication Date
- 2025-01-03
AI Technical Summary
In traditional electrolytic hydrogen production technology, the porosity and catalytic activity of the cathode structure are difficult to improve simultaneously, and the cost is high, which limits its large-scale commercial application.
Porous nickel structures were prepared by plasma spraying and chemical activation, and Mn-doped ZnCoP transition metal phosphide coating was deposited on its surface. A two-step constant potential electrodeposition process was used to form a cathode structure with high porosity and high electrocatalytic performance.
It has achieved the increase of high porosity and high catalytic activity sites, improved electrocatalytic performance and long-term stability of materials, reduced costs, and is suitable for electrolytic seawater hydrogen production technology, with a wide range of clean energy application prospects.
Smart Images

Figure CN119243230A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemical catalysis, and in particular to a cathode structure with high porosity and high electrocatalytic performance and a preparation method thereof. Background Art
[0002] In the field of electrochemical catalysis, especially in the technology of hydrogen production by water electrolysis, the development of efficient, stable and cost-effective cathode structures is the key to achieving clean energy conversion. Traditional water electrolysis hydrogen production technology mostly uses precious metals such as platinum, ruthenium, iridium, etc. as catalysts. Although these materials have high catalytic activity, they are limited by resource scarcity and high cost, which seriously restricts their large-scale commercial application. In addition, although the materials such as nickel foam used in the prior art have a high porosity, they are limited in pore size and are expensive and not suitable for mass production.
[0003] In response to these challenges, researchers have been exploring catalysts based on non-precious metal elements in order to achieve the goal of efficiently catalyzing the hydrogen evolution reaction (HER). Some studies have prepared doped catalysts on nickel foam or carbon fiber cloth by means of hydrothermal method and electrodeposition method. Although these methods can improve the catalytic performance to a certain extent, it is difficult to achieve large-scale production, and there is still a lot of room for improvement in catalytic performance. Most of the existing research focuses on the microstructure regulation of materials. Further technological innovation and breakthroughs are still needed to achieve cathode structures with high porosity, high catalytic activity and high stability. Summary of the invention
[0004] In view of the above shortcomings of the prior art, the present invention provides a cathode structure with high porosity and high electrocatalytic performance to solve the shortcomings of the traditional cathode structure of the catalytic electrode material for hydrogen production by electrolysis of water in achieving high porosity, enhancing electrocatalytic activity and improving long-term stability.
[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0006] A method for preparing a cathode structure with high porosity and high electrocatalytic performance, the method comprising the following steps:
[0007] S1: uniformly mixing Ni and Al powders in a certain proportion, and uniformly spraying the mixed powders onto the surface of the nickel mesh by a plasma spraying method to obtain a NiAl alloy coating;
[0008] S2: using a chemical activation treatment method, using specific chemical reagents and conditions, to remove the Al element in the NiAl alloy coating obtained in step S1, thereby forming a porous nickel structure with high porosity;
[0009] S3: performing a pretreatment operation on the surface of the porous nickel structure obtained in step S2 to remove oil stains and oxides on the surface of the porous nickel structure;
[0010] S4: Using a two-step constant potential electrodeposition method, a Mn-doped ZnCoP transition metal phosphide coating is deposited on the surface of the porous nickel structure pretreated in step S3 to obtain the cathode structure, i.e., a nickel-based MnZnCoP water electrolysis catalytic electrode. The present invention can expand the morphology size of the catalyst and expose more active sites by introducing Mn. Designing an appropriate phosphorus atomic weight can improve HER activity within a certain range and increase the number of hydrogen evolution active sites; Mn replaces part of Co in CoP to enhance the transfer of electrons to P, and makes the thermal neutral hydrogen adsorption free energy (△GH) of the catalyst close to 0, which is conducive to the adsorption and desorption of hydrogen. The interaction between Mn and Co is also conducive to the electrocatalytic hydrogen evolution reaction. This synergistic strategy is used to more efficiently improve the electrocatalytic performance. In addition, the catalyst of the present invention is directly deposited on the porous nickel base without the use of a binder, which increases the hydrogen evolution active sites on the basis of improving the electrode conductivity.
[0011] As a preferred technical solution, in step S1, the mixing volume ratio of the Ni and Al powders is 40-90:10-60.
[0012] As a preferred technical solution, in step S1, the parameters of the plasma spraying include power of 20-50KW, powder feeding rate of 30-70g / min, spraying distance of 50-200mm, and spraying speed of 50-400mm / s.
[0013] As a preferred technical solution, in step S2, the chemical reagent used in the chemical activation treatment method is a mixed solution composed of 20-40wt% potassium sodium tartrate and 10-20wt% strong alkali.
[0014] As a preferred technical solution, the strong base is sodium hydroxide or potassium hydroxide.
[0015] As a preferred technical solution, in step S2, the specific conditions used in the chemical activation treatment method are treatment at 60 to 80°C for 12 to 36 hours.
[0016] As a preferred technical solution, in step S3, the surface of the porous nickel structure is pretreated by ultrasonic cleaning in anhydrous ethanol, deionized water, dilute hydrochloric acid and deionized water for 20 to 40 minutes respectively.
[0017] As a preferred technical solution, in step S4, the first step of constant potential electrodeposition uses an electrolyte composed of 0.1-0.3 mol / L MnCl2·4H2O, 0.01-0.03 mol / L CH3COOH, 0.3-0.7 mol / L NaCl and 0.1-0.3 mol / L NaH2PO2·H2O, and the electrodeposition is carried out at a constant potential of -1.0V to -2.0V for 5 to 20 minutes.
[0018] As a preferred technical solution, in step S4, the second step of constant potential electrodeposition uses an electrolyte composed of 0.05-0.10 mol / L CoSO4·7H2O, 0.5-2.0 mol / L ZnCl2, 0.01-0.03 mol / L CH3COOH, 0.3-0.7 mol / L NaCl and 0.05-0.10 mol / L NaH2PO2·H2O, and deposition is carried out at a potential of -1.0V to -2.0VV for 20 to 30 minutes.
[0019] Another aspect of the present invention is to provide a cathode structure with high porosity and high electrocatalytic performance, wherein the cathode structure is prepared by the method for preparing a cathode structure with high porosity and high electrocatalytic performance as described above.
[0020] Beneficial effects of the present invention:
[0021] The method for preparing a cathode structure with high porosity and high electrocatalytic performance of the present invention innovatively proposes to prepare a porous nickel structure substrate by plasma spraying and chemical activation, and at the same time combines the two-step constant potential electrodeposition process of introducing Mn doping, which not only realizes the uniform composite of a porous nickel substrate with high porosity and a Mn-doped ZnCoP active layer, but also realizes a significant increase in catalytic active sites and optimization of the electronic structure. This design not only enhances the electrocatalytic activity and reaction kinetics of the catalytic electrode, but also maintains the long-term stability and structural integrity of the material, which helps to improve the efficiency and application potential of hydrogen production by electrolysis of water.
[0022] In general, the cathode structure prepared by the present invention can be used as an electrode material for electrolyzing seawater to produce hydrogen. It not only has high porosity and efficient and stable HER activity, but also still shows good catalytic activity and stability in harsh environments such as alkaline solutions. It has strong overall comprehensive performance and environmental adaptability, can meet the long-term durability and stability requirements of electrolyzing water to produce hydrogen technology, and has a wide range of application prospects in the field of clean energy production. In addition, the catalyst preparation method of the cathode structure of the present invention can be prepared in batches, which has the advantage of lower cost compared to commonly used electrolyzing water catalysts (such as precious metals platinum, ruthenium, iridium, etc.). BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1Optical microscope photos and scanning electron microscope (SEM) images of commercial pure nickel mesh.
[0024] Figure 2 These are optical microscope photos and scanning electron microscope (SEM) images of the cathode structure prepared in Example 1 of the present invention.
[0025] Figure 3 This is a cross-sectional pore distribution diagram of the cathode structure prepared in Example 1 of the present invention.
[0026] Figure 4 HER test performance diagram of cathode structure samples prepared in Example 1 of the present invention and Comparative Examples 1 to 3. DETAILED DESCRIPTION
[0027] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0028] Example 1
[0029] The method for preparing a cathode structure with high porosity and high electrocatalytic performance in this embodiment comprises the following steps:
[0030] S1: Ni and Al powders with a volume ratio of 80:20 are mixed uniformly, and the mixed powders are uniformly sprayed onto the surface of a 60-mesh nickel mesh by a plasma spraying method to obtain a NiAl alloy coating. The parameters of the plasma spraying include power 36KW, powder feeding rate 52g / min, spraying distance 150mm, and spraying speed 250mm / s.
[0031] S2: using a chemical activation treatment method, using specific chemical reagents and conditions to remove the Al element in the NiAl alloy coating obtained in step S1, and forming a porous nickel structure with high porosity; the chemical reagent used in the chemical activation treatment method is a mixed aqueous solution composed of 30wt% potassium sodium tartrate and 10wt% sodium hydroxide. The specific conditions used in the chemical activation treatment method are treatment at 70°C for 24 hours.
[0032] S3: performing a pretreatment operation on the surface of the porous nickel structure obtained in step S2 to remove oil stains and oxides on the surface of the porous nickel structure; the pretreatment operation on the surface of the porous nickel structure is ultrasonic cleaning in anhydrous ethanol, deionized water, dilute hydrochloric acid and deionized water for 20 minutes each.
[0033] S4: Using a two-step constant potential electrodeposition method, a Mn-doped ZnCoP transition metal phosphide coating is deposited on the surface of the porous nickel structure pretreated in step S3 to obtain the cathode structure, i.e., a nickel-based MnZnCoP water electrolysis catalytic electrode (corresponding to Figure 4The first step of constant potential electrodeposition uses an electrolyte composed of 0.225 mol / L MnCl·4H2O, 0.02 mol / L CH3COOH, 0.5 mol / L NaCl and 0.225 mol / L NaH2PO2·H2O, and the electrodeposition is carried out at a constant potential of -1.6 V (relative to SCE) for 10 minutes. The second step of constant potential electrodeposition uses an electrolyte composed of 0.075 mol / L CoSO4·7H2O, 1.0 mol / L ZnCl2, 0.02 mol / L CH3COOH, 0.5 mol / L NaCl and 0.075 mol / L NaH2PO2·H2O, and the deposition is carried out at a potential of -1.6 V (relative to SCE) for 20 minutes.
[0034] The catalyst structure characterization results show that Figure 1 and Figure 2 It can be seen that the porous nickel mesh prepared in this embodiment has a rough surface and a large surface area; a large amount of catalyst is loaded on the surface of the porous nickel mesh. This structure increases the specific surface area of the material and can provide more active sites, thereby helping to improve its overall catalytic activity. Figure 3 It can be further seen that there are a large number of pores in the cathode structure, which is also one of the direct evidences of the high porosity of the electrode.
[0035] Comparative Example 1
[0036] The preparation method of the cathode structure of this comparative example has the same operation steps as Example 1, except that this comparative example does not include step S4, and the corresponding Figure 4 Homemade spray nickel catalyst.
[0037] Comparative Example 2
[0038] In this comparative example, Ni powder is sprayed uniformly onto the surface of a 60-mesh nickel mesh by a plasma spraying method. The parameters of the plasma spraying include power 36KW, powder feeding rate 52g / min, spraying distance 150mm, and spraying speed 250mm / s. Figure 4 A commercial nickel catalyst was sprayed on the
[0039] Comparative Example 3
[0040] This control example is a 60-mesh commercial pure nickel mesh, corresponding to Figure 4 Medium pure nickel mesh.
[0041] The samples of Example 1 and Comparative Examples 1, 2, and 3 were used to test their electrochemical properties in the following steps. The samples prepared in Example 1 and Comparative Examples 1, 2, and 3 were fixed with sample clamps and used as working electrodes (cathodes) in turn, with commercial nickel mesh as anode and Ag / AgCl (saturated KCl solution) as reference electrode, in a 1.0 mol / L KOH solution, scanning from 1.0 V to 2.2 V. The test conditions were: 25°C.
[0042] The electrochemical test results show that Figure 4 As shown, the MnZnCoP / Ni catalyst prepared in Example 1 has a lower polarization potential and a higher catalytic activity than other control examples. The MnZnCoP / Ni catalyst prepared in Example 1 has the best performance, and the current density can reach 270 mA / cm 2 @2.0V, the performance of the porous Ni cathode catalyst prepared by spraying in Comparative Example 1 (self-made sprayed nickel catalyst) is second, which is 240mA / cm 2 @2.0V, the performance of the spray-coated Ni cathode catalyst (spray-coated commercial nickel catalyst) in Comparative Example 2 was poor at 210 mA / cm 2 @2.0V, the worst catalytic performance of commercial pure nickel mesh is 60mA / cm 2 @2.0 V. This indicates that the cathode structure (MnZnCoP / Ni catalyst) prepared in Example 1 has excellent catalytic performance for hydrogen production by water electrolysis.
[0043] Example 2
[0044] The method for preparing a cathode structure with high porosity and high electrocatalytic performance in this embodiment comprises the following steps:
[0045] S1: Ni and Al powders with a volume ratio of 90:10 are uniformly mixed, and the mixed powders are uniformly sprayed onto the surface of a 60-mesh nickel mesh by a plasma spraying method to obtain a NiAl alloy coating. The parameters of the plasma spraying include power 20KW, powder feeding rate 30g / min, spraying distance 50mm, and spraying speed 50mm / s.
[0046] S2: using a chemical activation treatment method, using specific chemical reagents and conditions to remove the Al element in the NiAl alloy coating obtained in step S1, and forming a porous nickel structure with high porosity; the chemical reagent used in the chemical activation treatment method is a mixed aqueous solution composed of 20wt% potassium sodium tartrate and 20wt% sodium hydroxide. The specific conditions used in the chemical activation treatment method are treatment at 60°C for 36 hours.
[0047] S3: performing a pretreatment operation on the surface of the porous nickel structure obtained in step S2 to remove oil stains and oxides on the surface of the porous nickel structure; the pretreatment operation on the surface of the porous nickel structure is ultrasonic cleaning in anhydrous ethanol, deionized water, dilute hydrochloric acid and deionized water for 20 minutes each.
[0048] S4: Using a two-step constant potential electrodeposition method, a Mn-doped ZnCoP transition metal phosphide coating is deposited on the surface of the porous nickel structure pretreated in step S3 to obtain the cathode structure, i.e., a nickel-based MnZnCoP water electrolysis catalytic electrode. The first step of constant potential electrodeposition uses an electrolyte consisting of 0.10 mol / L MnCl·4H2O, 0.01 mol / L CH3COOH, 0.7 mol / L NaCl and 0.3 mol / L NaH2PO2·H2O, and electrodeposition is performed at a constant potential of -1.0 V (relative to SCE) for 20 minutes. The second step of constant potential electrodeposition uses an electrolyte composed of 0.05 mol / L CoSO4·7H2O, 0.5 mol / L ZnCl2, 0.01 mol / L CH3COOH, 0.3 mol / L NaCl and 0.05 mol / L NaH2PO2·H2O, and the deposition is carried out at a potential of -1.0 V (relative to SCE) for 30 minutes.
[0049] The electrochemical test results show that the current density of the MnZnCoP / Ni catalyst prepared in this example can reach 260 mA / cm 2 @2.0V.
[0050] Example 3
[0051] The method for preparing a cathode structure with high porosity and high electrocatalytic performance in this embodiment comprises the following steps:
[0052] S1: Ni and Al powders with a volume ratio of 40:60 are uniformly mixed, and the mixed powders are uniformly sprayed onto the surface of a 60-mesh nickel mesh by a plasma spraying method to obtain a NiAl alloy coating. The parameters of the plasma spraying include power 50KW, powder feeding rate 70g / min, spraying distance 200mm, and spraying speed 400mm / s.
[0053] S2: using a chemical activation treatment method, using specific chemical reagents and conditions to remove the Al element in the NiAl alloy coating obtained in step S1, and forming a porous nickel structure with high porosity; the chemical reagent used in the chemical activation treatment method is a mixed aqueous solution composed of 40wt% potassium sodium tartrate and 10wt% sodium hydroxide. The specific conditions used in the chemical activation treatment method are treatment at 80°C for 12 hours.
[0054] S3: performing a pretreatment operation on the surface of the porous nickel structure obtained in step S2 to remove oil stains and oxides on the surface of the porous nickel structure; the pretreatment operation on the surface of the porous nickel structure is ultrasonic cleaning in anhydrous ethanol, deionized water, dilute hydrochloric acid and deionized water for 40 minutes each.
[0055] S4: Using a two-step constant potential electrodeposition method, a Mn-doped ZnCoP transition metal phosphide coating is deposited on the surface of the porous nickel structure pretreated in step S3 to obtain the cathode structure, i.e., a nickel-based MnZnCoP water electrolysis catalytic electrode. The first step of constant potential electrodeposition uses an electrolyte consisting of 0.3 mol / L MnCl·4H2O, 0.03 mol / L CH3COOH, 0.3 mol / L NaCl and 0.1 mol / L NaH2PO2·H2O, and electrodeposition is performed at a constant potential of -2.0 V (relative to SCE) for 5 minutes. The second step of constant potential electrodeposition uses an electrolyte composed of 0.1 mol / L CoSO4·7H2O, 2.0 mol / L ZnCl2, 0.03 mol / L CH3COOH, 0.7 mol / L NaCl and 0.10 mol / L NaH2PO2·H2O, and the deposition is carried out at a potential of -2.0 V (relative to SCE) for 20 minutes.
[0056] The electrochemical test results show that the current density of the MnZnCoP / Ni catalyst prepared in this example can reach 255 mA / cm 2 @2.0V.
[0057] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention claimed.
Claims
1. A method for preparing a cathode structure with high porosity and high electrocatalytic performance, characterized in that: The preparation method comprises the following steps: S1: uniformly mixing Ni and Al powders in a certain proportion, and uniformly spraying the mixed powders onto the surface of the nickel mesh by a plasma spraying method to obtain a NiAl alloy coating; S2: using a chemical activation treatment method, using specific chemical reagents and conditions, to remove the Al element in the NiAl alloy coating obtained in step S1, thereby forming a porous nickel structure with high porosity; S3: performing a pretreatment operation on the surface of the porous nickel structure obtained in step S2 to remove oil stains and oxides on the surface of the porous nickel structure; S4: using a two-step constant potential electrodeposition method, depositing a Mn-doped ZnCoP transition metal phosphide coating on the surface of the porous nickel structure pretreated in step S3 to obtain the cathode structure, i.e., a nickel-based MnZnCoP water electrolysis catalytic electrode.
2. The method for preparing a cathode structure with high porosity and high electrocatalytic performance according to claim 1, characterized in that: In step S1, the mixing volume ratio of the Ni and Al powders is 40-90:10-60.
3. The method for preparing a cathode structure with high porosity and high electrocatalytic performance according to claim 1, characterized in that: In step S1, the parameters of the plasma spraying include power of 20-50KW, powder feeding rate of 30-70g / min, spraying distance of 50-200mm, and spraying speed of 50-400mm / s.
4. The method for preparing a cathode structure with high porosity and high electrocatalytic performance according to claim 1, characterized in that: In step S2, the chemical reagent used in the chemical activation treatment method is a mixed solution composed of 20-40wt% potassium sodium tartrate and 10-20wt% strong alkali.
5. The method for preparing a cathode structure with high porosity and high electrocatalytic performance according to claim 4, characterized in that: The strong base is sodium hydroxide or potassium hydroxide.
6. The method for preparing a cathode structure with high porosity and high electrocatalytic performance according to claim 1, characterized in that: In step S2, the specific conditions used in the chemical activation treatment method are treatment at 60-80°C for 12-36 hours.
7. The method for preparing a cathode structure with high porosity and high electrocatalytic performance according to claim 1, characterized in that: In step S3, the surface of the porous nickel structure is pretreated by ultrasonic cleaning in anhydrous ethanol, deionized water, dilute hydrochloric acid and deionized water for 20 to 40 minutes respectively.
8. The method for preparing a cathode structure with high porosity and high electrocatalytic performance according to claim 1, characterized in that: In step S4, the first step of constant potential electrodeposition uses an electrolyte composed of 0.1-0.3 mol / L MnCl2·4H2O, 0.01-0.03 mol / L CH3COOH, 0.3-0.7 mol / L NaCl and 0.1-0.3 mol / L NaH2PO2·H2O, and the electrodeposition is carried out at a constant potential of -1.0V to -2.0V for 5 to 20 minutes.
9. The method for preparing a cathode structure with high porosity and high electrocatalytic performance according to claim 1, characterized in that: In step S4, the second step of constant potential electrodeposition uses an electrolyte composed of 0.05-0.10 mol / L CoSO4·7H2O, 0.5-2.0 mol / L ZnCl2, 0.01-0.03 mol / L CH3COOH, 0.3-0.7 mol / L NaCl and 0.05-0.10 mol / L NaH2PO2·H2O, and deposition is carried out at a potential of -1.0V to -2.0V for 20 to 30 minutes.
10. A cathode structure with high porosity and high electrocatalytic performance, characterized in that: The cathode structure is prepared by the method for preparing a cathode structure with high porosity and high electrocatalytic performance as described in any one of claims 1 to 9.
